Signifikansi Pengaruh Sentimen Pemberlakuan PSBB Terhadap Aspek Ekonomi: Pengaruh Pada Nilai Tukar Rupiah dan Stock Return (Studi Kasus Pandemi Covid-19) - Irma Lestari Made (Jurnal Bina Akuntansi, 2020)
The Large-Scale Social Limitation Policy (Pembatasan Sosial Berskala Besar/PSBB) was chosen by the Indonesian government in responding to the pandemic covid-19. The PSBB policy is preferred by the government to be implemented instead of lockdown. Much controversy in public over the PSBB policy has built the sentiment. Consideration of the economic aspects has been the main reason in making these policies. With consideration of the state of the Indonesian economy, the government believes that this policy is an effective and efficient pathway with a note that the public will be able to conduct pandemic covid-19 health protocol discipline and form herd immunity. This study aims to evaluate the effect of the implementation of the PSBB which has an impact on public sentiment fluctuations, using secondary stock return data on blue-chip stocks and the rupiah exchange rate in the range of time before and after the implementation of the PSBB begun, April 10, 2020. Wilcoxon test is used as data analysis tool of nonparametric statistics. The test results stated that the exchange rate of the rupiah against the US dollar was significantly affected by public sentiment towards the implementation of the PSBB, while the stock return was not significantly affected. Several factors beyond the implementation of PSBB need to be considered in influencing stock returns as well as the rupiah exchange rate.